2022
DOI: 10.3390/ma15124145
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of Clear Aligner Composite Attachments to Ceramic Materials: An In Vitro Study

Abstract: Background: We aim to evaluate the effect of surface conditioning, bonding agents and composite types on surface roughness (SR) and shear bond strength (SBS) of clear aligner composite attachments bonded to ceramics. Methods: One hundred and eighty IPS e.max CAD specimens were prepared. For SR, 60 specimens were divided according to surface conditioning (n = 15) into four groups: control, 9.6% hydrofluoric acid (HFA), 37% phosphoric acid (PhA), air abrasion (AA). SR was measured using a Profilometer and Atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Wener Chen pointed out that the SBS of attachment was about 20 Mpa (Chen et al, 2021). Our results in experiment group had not much difference with the relevant results in previous study (Chu et al, 2015;Chen et al, 2021;Alsaud et al, 2022). This phenomenon proved that sustained release hydrogen peroxide bleaching treatment over 40 days would not reduce the SBS of the attachment on the isolated teeth to some extent.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Wener Chen pointed out that the SBS of attachment was about 20 Mpa (Chen et al, 2021). Our results in experiment group had not much difference with the relevant results in previous study (Chu et al, 2015;Chen et al, 2021;Alsaud et al, 2022). This phenomenon proved that sustained release hydrogen peroxide bleaching treatment over 40 days would not reduce the SBS of the attachment on the isolated teeth to some extent.…”
Section: Discussionsupporting
confidence: 55%
“…The attachment consists of a composite resin bonded to the tooth surface. Adhesion failure may lead to attachment loss on the tooth surface (Abu Alhaija et al, 2010;Alsaud et al, 2022); this loss may cause significant clinical problems, including prolonged treatment time, increased frequency of review, and affect the prognosis of treatment (Dasy et al, 2015). Previous study has shown that the adhesive strength of brackets decreased, irrespective of whether 25%-35% hydrogen peroxide or 10%-20% urea peroxide gel is used (Lima et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies perfectly described model assumption and validity according to the standards [22,30,35], and another three [21,32,37] were characterized by minor shortcomings. Eight studies [16,[18][19][20]24,26,28,40] were subjected to analysis with the QUIN assessment tool. All of the in vitro studies clearly described the aim.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…All of the in vitro studies clearly described the aim. Only three [16,18,19] performed a proper sample size calculation. In five studies, the sampling technique was clearly described, while in three, minor flow clouds were observed.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%